2021
DOI: 10.3390/nano12010133
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nano-Sized Energetic Materials (nEMs) on the Performance of Solid Propellants: A Review

Abstract: As a hot research topic, nano-scale energetic materials have recently attracted much attention in the fields of propellants and explosives. The preparation of different types of nano-sized energetic materials were carried out, and the effects of nano-sized energetic materials (nEMs) on the properties of solid propellants and explosives were investigated and compared with those of micro-sized ones, placing emphasis on the investigation of the hazardous properties, which could be useable for solid rocket nozzle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 39 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…When undertaking material synthesis, it is imperative to satisfy certain requisite criteria, including the capability to work with diverse material systems, produce particles spanning a wide and controllable size range, and mitigate the formation of impurities, spontaneous reactions, and agglomeration phenomena while concurrently maintaining elevated levels of productivity and economic viability and ensuring reproducibility of the resultant characteristics [76][77][78][79][80][81][82][83][84][85][86][87][88][89]. As shown in Figure 2, the synthesis techniques specifically tailored for thermite applications and their suitability are contingent upon the specific performance requirements and criteria, offering a multitude of advantages and trade-offs [76][77][78][79][80][81][82][83][84][85][86][87][88][89]. The sol-gel method facilitates the judicious tailoring of the chemical composition of the gel matrices by means of combining precursors, thereby enabling the deliberate modulation of the resultant material properties [90,91].…”
Section: Synthesis Methods Of Composite Energetic Materialsmentioning
confidence: 99%
“…When undertaking material synthesis, it is imperative to satisfy certain requisite criteria, including the capability to work with diverse material systems, produce particles spanning a wide and controllable size range, and mitigate the formation of impurities, spontaneous reactions, and agglomeration phenomena while concurrently maintaining elevated levels of productivity and economic viability and ensuring reproducibility of the resultant characteristics [76][77][78][79][80][81][82][83][84][85][86][87][88][89]. As shown in Figure 2, the synthesis techniques specifically tailored for thermite applications and their suitability are contingent upon the specific performance requirements and criteria, offering a multitude of advantages and trade-offs [76][77][78][79][80][81][82][83][84][85][86][87][88][89]. The sol-gel method facilitates the judicious tailoring of the chemical composition of the gel matrices by means of combining precursors, thereby enabling the deliberate modulation of the resultant material properties [90,91].…”
Section: Synthesis Methods Of Composite Energetic Materialsmentioning
confidence: 99%
“…Numerous experimental studies have confirmed that nanosized EMs can be considered as a source of extremely high heat release rates along with outstanding possibilities of burning rates for programming, reliability, extremely high burning efficiency, safety of use and reduced sensitivity to external influences [ 19 , 20 ]. The fundamental distinguishing feature of the nanosized EMs is a significant increase in the specific surface area and a decrease in the distances between nanocomponents, which provides a significant increase in the chemical reaction rates while simultaneously providing a reduction of the ignition delay, as well as providing the required safety level [ 20 ].…”
Section: Game-changing Transformative Energetics Conceptmentioning
confidence: 99%
“…In addition to possessing high energy, having the controllable reaction rate and acceptable safety are another two requirements for energetic materials used in military ammunition [ 13 ]. The preparation of nanosized energetic materials has made it possible to achieve those targets, owing to the bigger surface to volume ratio and the higher reactivity that the nano-energetic materials have compared to common micro-energetic materials [ 14 , 15 , 16 ]. The higher reactivity of nanosized NC has great potential to improve the combustion performance of propellants or explosives [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%